ANALISIS MEDIASI PSYCHOLOGICAL EMPOWERMENT PADA PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP KINERJA KARYAWAN SUPPERDAZZLE YOGYAKARTA - Nurhidayat, Ahmad Wahyu; Kurniawan, Ignatius Soni; Purnamarini, Tri Ratna (STKIP Persada Khatulistiwa Sintang, 2024)
Employee performance research is still popular in various organizations, including for-profit companies. Performance issues are also a concern in Supperdazzle; not all employees consistently meet sales targets, consumer complaints regarding service performance have not been fully handled, tasks are not completed on time, employees are not ready to work according to standard operational procedures. This study is intended to analyze the impact of perceived organizational support (POS) on task performance through psychological empowerment (PE). The research method used is a quantitative method. Researchers determined all 49 SupperDazzle employees as respondents through a questionnaire and analyzed using the classic assumption test and using multiple linear regression. This classic assumption test includes normality, multicollinearity and heteroscedasticity tests. Mediation testing uses the Sobel test. The results showed a positive influence of POS and PE on task performance. The significant influence of POS on PE also has an impact on the mediating role of PE on the influence of POS on task performance. Organizations can strengthen antecedents to improve employee performance.